2007
DOI: 10.1366/000370207779947440
|View full text |Cite
|
Sign up to set email alerts
|

Absorption Cross-Sections of the C—H Overtone of Volatile Organic Compounds: 2 Methyl-1,3-Butadiene (Isoprene), 1,3-Butadiene, and 2,3-Dimethyl-1,3-Butadiene

Abstract: Many molecules or transient radicals have well-documented absorption cross-sections in the ultraviolet (UV) region, but their absorption cross-sections in the near-infrared (NIR) region are much less often known and are difficult to measure. We propose a method to determine the unknown NIR absorption cross-sections using the known absorption cross-sections in the UV region, in which single-path UV absorption spectroscopy and NIR continuous wave cavity ringdown spectroscopy (cw-CRDS) are employed in a cross-arm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2008
2008
2025
2025

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 26 publications
0
21
0
Order By: Relevance
“…2) are in reasonable agreement with other reported values determined with a diode laser (2.5 Â 10 À22 cm 2 at 1651.52 nm). 21 Some data are used to extract the wavelength dependent mirror reflectivity when analysing the cavity enhanced datasets, and the resulting reflectivity is then used to correct the cavity enhanced absorption of different datasets (see Fig. 3).…”
Section: Resultsmentioning
confidence: 99%
“…2) are in reasonable agreement with other reported values determined with a diode laser (2.5 Â 10 À22 cm 2 at 1651.52 nm). 21 Some data are used to extract the wavelength dependent mirror reflectivity when analysing the cavity enhanced datasets, and the resulting reflectivity is then used to correct the cavity enhanced absorption of different datasets (see Fig. 3).…”
Section: Resultsmentioning
confidence: 99%
“…While the consensus in the literature supports this conclusion, there has been some dispute regarding the scis conformer (Fig. 2b), its fractional abundance at room temperature, and whether the conformer is planar or gauche (Traetteberg et al, 1984;Bock et al, 1987;Cias et al, 2007;Panchenko and De Mare, 2008;Squillacote and Liang, 2005;Allodi et al, 2008). Compton Squillacote and Liang (2005) using the G3B3 method.…”
Section: Vibrational Assignmentsmentioning
confidence: 98%
“…Despite the obvious need for quantitative infrared data and the potential for infrared observation of isoprene, as well as the relative abundance of UV cross sections (e.g., Campuzano-Jost et al, 2004, 2000, the only quantitative infrared intensity studies of isoprene found in the literature report absorption cross sections in the near-infrared (Denzer et al, 2011;Cias et al, 2007). While it is not unusual to record quantitative measurements of isoprene in conjunction with other experiments or for calibration purposes, these results are seldom reported in the literature.…”
Section: S Brauer Et Al: Isoprene Cross Sectionsmentioning
confidence: 99%
See 1 more Smart Citation
“…This method has been successfully used in several ringdown research studies and applications. (17,46,57,58,62,64,113,114) …”
Section: Electronicsmentioning
confidence: 99%